(untitled) (Research, Society and Development, 2021)
Cryptosporidiosis is a reemerging disease, responsible for serious public health problems worldwide, caused by the protozoan Cryptosporidium spp. with high zoonotic power, being able to contaminate food, water, and soil, and causing outbreaks of diarrhea, leading to economic and social losses. The objective of this study was to evaluate the occurrence of cryptosporidiosis in patients seen at a public hospital in Recife-PE. 247 records were evaluated from 2012 to 2020, with 89 cases of cryptosporidiosis. To confirm the diagnosis, Ritchie concentration and Kinyoun staining techniques were used. It was observed that there is a relationship between rainfall and the occurrence of cryptosporidiosis, which was confirmed between the registration of the number of cases and rainfall in the region with the highest number of cases. The research did not reveal statistical differences between sexes or ages between cases, but it diverged from other studies when it showed that the groups of patients were the oldest adults (75,3%) and the elderly (16,9%). We cannot rule out the hypothesis that the number of Emergency Units -UPAs by Regional Health Management can influence the chance of disease diagnosis. Further studies will be necessary to demystify its occurrence in the elderly, as well as its notification.